AIR LIMBAH LAUNDRY : KARAKTERISTIK DAN PENGARUHNYA TERHADAP KUALITAS AIR - Yuliana Yuliana; Markus Heryanto Langsa; Alfhons D. Sirampun (Jurnal Natural, 2020)
At present the laundry business is one of the promising businesses with targeted consumers from the upper middle class who do not have much time to wash clothes at home. Like other industries, laundry also produces wastewater that can have a negative impact on the environment if it is not managed properly. This study characterizes laundry wastewater and looks at its effect on the quality to the groundwater/wells close to the laundry business. Water samples include TSS, TDS, Turbidity, pH , COD, BOD, Phosphate, and Detergent parameters analyzed according to SNI and/or the HACH method (DR3900). Characterization of the laundry wastewater samples show a high level of detergent and phosphate parameters ranging from 27,7-39,4 mg/L and 6,1-27,1 mg/L, respectively with the highest levels corresponds to Laundry wastewater samples at Jalan Baru. The detergent and phosphate contents in all well water samples are still below the required quality standard. Although the concentrations of parameters analysed in the laundry wastewater are very high and above the guidance, it is obvious from the well water samples results that there is no effect of laundry waste waters to the quality of ground waters.